RESTORASI EKOSISTEM MANGROVE BERBASIS MEDIA BIODEGRADABLE DI PESISIR DESA POKA - Sophia Fendjalang; Gino V. Limmon; Gratia D. Manuputty (Universitas Mataram, 2023)
Mangrove ecosystems have potential both ecologically, economically, physically, and chemically, but pressure from anthropogenic activities has resulted in increased degradation of mangrove ecosystems. Poka Village has several mangrove areas that have been damaged either by land clearing or by industrial waste. Therefore, ecosystem restoration was carried out in the coastal waters of Poka Village using biodegradable materials (BESE-Elements), where this activity is a community service activity, in collaboration with the Maritime Center of Pattimura University and Wardeenburg Ecology - The Netherlands. This activity was carried out for 2 days, where the seeds and propagules used came from the nursery center in Passo Negeri, the BESE-Element used was a product brought from the Netherlands, the planting was carried out by groups of students, lecturers, and the Wardeenburg team, which consisted of the preparation stage BESE-Element, making layouts for planting points, planting seeds and propagules, and installing protective nets. The result of the activity is that mangrove ecosystem restoration is carried out in semi-enclosed areas using 10 BESE-Element. Each BESE-Element was planted with 10 mangrove seedlings consisting of 5 seedlings and 5 propagules with an average height of 30-40 cm, the spacing between BESE-Element was 60 cm. The types of mangrove species planted were Bruguiera gymnorrhiza, Rhizophora apicutala, and Rhizophora stylosa. Around BESE-Elements planted seedlings and mangrove propagules as a control for mangroves in BESE-Elements. The results of this activity are expected to be able to overcome the degradation of the mangrove ecosystem that has occurred in the coastal area of ​​Poka Village and have good implications for improving the condition of the mangrove ecosystem both physically, ecologically, and economically.